Synthesis and characterization of monolayer molybdenum disulphide - Wang, S (2017)
Monolayer molybdenum disulphide (MoS2) is a semiconductor with a direct bandgap of ∼1.9 eV. Much research attention has been attracted to its potential applications in nanoelectronics and optoelectronics recently, all of which are based upon a scalable production of high-quality monolayer MoS2 and the in-depth comprehension of its fundamental properties. The PhD project focused on developing chemical vapour deposition (CVD) methods to grow monolayer MoS2 and its related two-dimensional (2D) vertical heterostructures with an understanding of the growth mechanism. Subsequently, a range of characterizations were conducted to investigate the structural, vibrational, optical and mechanical properties of as-grown samples. An atmospheric-pressure CVD (APCVD) approach was first developed to grow monolayer MoS2 crystals on silicon substrates with a 300 nm oxide layer (SiO2/Si) by using molybdenum trioxide (MoO3) and sulphur (S) as precursors. A sharp gradient of MoO3 was intentionally created, which induced a location-dependent shape evolution of MoS2 domains. A qualitative explanation was proposed, attributing this phenomenon to local changes in the Mo:S ratio of precursors and its influence on the kinetic growth dynamics of edges. Subsequently, the CVD setup was improved in both the precursor loading manner and the substrate orientation to achieve centimetre-scale monolayer MoS2 films with large domain sizes of 10-20μm. Finally, 2D MoS2/hexagonal boron nitride (h-BN) vertical heterostructures were fabricated via an all-CVD method. Raman and photoluminescence (PL) spectroscopy were applied to show its merits of smaller lattice strain, lower doping level and better interlayer contact compared with CVD-grown MoS2 on SiO2/Si substrates and mechanically stacked samples. Aberration-corrected transmission electron microscopy (AC-TEM) was carried out to study the defect structure and fracture mechanics of monolayer MoS2 at a single atom level. Subtle lattice reconstructions of line defects in various lengths and widths were resolved. Density functional theory (DFT) predicted a reduction of the bandgap as the line defects broaden, which eventually makes them behave as metallic channels embedded in the semiconducting MoS2. Another joint experimental and theoretical study was conducted to track the real-time crack propagation in monolayer MoS2. The atomically sharp crack tip went through the preferential lattice direction with least energy release. Increasing defect density was found to induce an enhanced fracture toughness and a fracture mechanism transition from brittle to ductile.